265WS Improving Guideline Implementability With Guide-M (Guideline Implementability For Decision Excellence Model): An Interactive Workshop. (15th August 2013) - Kastner, M; Makarski, J; Hayden, L; Durocher, L; Chatterjee, A; Bhattacharyya, O; Brouwers, M
Abstract : Background: We developed a framework of guideline uptake called GuIDE-M (Guideline Implementability for Decision Excellence-Model) based on an extensive literature review. It describes four domains covering guideline content to optimise the implementability of recommendations (Stakeholder development, Evidence synthesis, Considered Judgement and Feasibility) and two domains related to communication of content (Language and Format). Objectives/Goal: (1) To learn about GuIDE-M, (2) To conduct an assessment of participants' current use of the GuIDE-M domains in guideline development or assessment and (3) To determine priorities for tool development to operationalize GuIDE-M domains. Target Group, Suggested Audience: Guideline developers, guideline users and researchers. [5] Description of the Workshop and Methods used to Facilitate Interactions: (1) Introduction (15 minutes). A brief foundational overview of GuIDE-M. (2) Facilitated Assessment (60 minutes). Participants will break into small groups to discuss one or more of the domains in GuIDE-M. There they will (a) conduct a more detailed review of the domain, (b) assess the extent to which their guideline-related activities align with GuIDE-M principles, (c) reflect on the extent to which improving in the area is a priority, (d) discuss methods and available tools to operationalize the domain concepts, and (e) explore the types of tool(s) that should be developed to incorporate domain concepts into guideline development. Participants will be invited to remain involved as evaluators, pilot-testers and developers of these tools. The facilitated assessment will happen twice (2 x 30 minutes) to allow participants to focus on two of the GuIDE-M domains. (3) Wrap-Up (15 minutes).